2012
DOI: 10.3386/w18597
|View full text |Cite
|
Sign up to set email alerts
|

Do Labor Market Policies Have Displacement Effects? Evidence from a Clustered Randomized Experiment

Abstract: This paper reports the results from a randomized experiment designed to evaluate the direct and indirect (displacement) impacts of job placement assistance on the labor market outcomes of young, educated job seekers in France. We use a two-step design. In the first step, the proportions of job seekers to be assigned to treatment (0%, 25%, 50%, 75% or100%) were randomly drawn for each of the 235 labor markets (e.g. cities) participating in the experiment. Then, in each labor market, eligible job seekers were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
257
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(267 citation statements)
references
References 14 publications
(18 reference statements)
5
257
0
3
Order By: Relevance
“…There is evidence that labor market programs can have displacement effects, i.e. the program may shift employment from ineligible to eligible jobs instead of creating more jobs overall (Crépon et al 2013).…”
Section: Displacement Effectsmentioning
confidence: 99%
“…There is evidence that labor market programs can have displacement effects, i.e. the program may shift employment from ineligible to eligible jobs instead of creating more jobs overall (Crépon et al 2013).…”
Section: Displacement Effectsmentioning
confidence: 99%
“…11 Moreover, in areas with a high level of treatment, the competition for jobs can increase, decreasing everyone's arrival rates. Based on Crépon et al (2013), one way to gauge the extent to which this is the case is to use the varying proportion of treated (out of the unemployed population) for each city and occupation. In the presence of negative externalities, an increased proportion of treated individuals should reduce overall formal employment rates.…”
Section: B Effects Of the Jóvenes En Acción On Participation In The mentioning
confidence: 99%
“…3 One concern is that some of the observed effects do not represent an increase in overall economic activity, but could arise from the displacement of other workers who are close substitutes of the trainees. Although evidence in Blundell et al (2004) showed no displacement effects in the United Kingdom, a specially designed randomized experiment evaluating a job placement program in France showed evidence of job displacement (see Crépon et al 2013). If the training does improve human capital, such displacement should only be a concern in the short run; in the longer run the economy should expand in response to increased resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crépon et al. () represents an apogee of this approach. In their study of a French active labour market program, they randomly assign both eligible individuals within jurisdictions and the fraction of the eligible population treated at the jurisdictional level.…”
Section: Spillovers and Other General Equilibrium Effectsmentioning
confidence: 99%